Who is motivated to learn in training offered by the companies? - Mourão, Luciana; Marins, Jesiane (Paidéia (Ribeirão Preto), 2010)
With the growing competitiveness of the market, the organizations have made Training and Development Programs aims better results. This survey had as its main objective to verify if the individual, training and organizational characteristics influence the results of motivation to learn. The sample was of 220 workers who would be trained in seven private companies of the Rio de Janeiro. The scales to measure the motivation to learn and beliefs about the training were previously validated. There were descriptive and standard multiple regression analyses. The results indicate that the beliefs about training, the kind of training, the kind of instructor and the time of work are determinants of motivation to learn. We discussed practical implications of the results and suggested agenda to search for the area.